1
$\begingroup$

When doing some exercises on Khan Academy, the following question came up: "The sum of 3 consecutive odd numbers is 69. What is the third number in this sequence?" My answer was 27 because I thought -Odd- Numbers to show up as = 1, 3, 5, 7, etc. Apparently, it consists of x, 2, 4, 6, etc. Can someone explain this to me?

  • English is not my first or second language in case I'm missing something..

KhanAcademy's Explanation

$\endgroup$
7
  • 1
    $\begingroup$ Your definition of odd is correct; $0, 2, 4, 6, ...$ are even numbers. 27 is wrong because 23 + 25 + 27 is 75, not 69. $\endgroup$ – user296602 Aug 10 '17 at 3:22
  • $\begingroup$ Uhm thanks but how did you get to 75? The answer is 25. $\endgroup$ – Eli S. Aug 10 '17 at 3:24
  • $\begingroup$ Let $x$ be an odd number, then $x+(x+2)+(x+4)=69$ implies $x=21$ so the third number is $25$ $\endgroup$ – Chinnapparaj R Aug 10 '17 at 3:24
  • 2
    $\begingroup$ @EliS. My point is that you can tell your answer is wrong because 23 + 25 + 27 = 75, as you can add by hand. $\endgroup$ – user296602 Aug 10 '17 at 3:25
  • $\begingroup$ Oh yeah, thanks user, I know it's wrong but I just didn't get why they used even numbers instead of odd numbers. Thanks Chinz, I get it now. Since x is 21 = Odd number, +2 is 23 + 4 is 25 which are all odd. Thanks! $\endgroup$ – Eli S. Aug 10 '17 at 3:27
0
$\begingroup$

Consecutive odd numbers differs $2$.

Now suppose $a$ is a odd numbers, then $a-2, a+2$ are also odd numbers.

Now it is given that $$a-2+a+a+2=69\\\Rightarrow 3a=69\\\Rightarrow a=23$$

Then the third number in this sequence is $a+2=25$ (Ans.)

$\endgroup$
2
$\begingroup$

Odd numbers refer to the number that are not divisible by 2. E.g. 1, 3, 5, ...

As for the question, we need to assume 3 consecutive odd numbers: x, x+2 and x+4. (the difference between 2 consecutive-odds is 2)

$$ x+x+2+x+4=69$$ $$ 3x+6=69$$ $$ 3x= 69-6=63 $$ $$ x={63\over 3} = 21$$

Hence, the third number is 21+4= 25.

$\endgroup$
1
  • $\begingroup$ Thanks Kummar, already solved it in the comments too. :) $\endgroup$ – Eli S. Aug 10 '17 at 3:45
0
$\begingroup$

Using arithmetic progression formula

$$S_n=\frac{n}{2}(a+l)$$

where a is the first term and l is the last term.

$$S_n=\frac{n}{2}(2a+(n-1)d)$$

$$S_3=69$$

The difference between two odd numbers is two.

odd number sequences

$$1,3,5,7,9...$$

It is obvious that the sequence is arithmetic and have a common difference,

$$3-1=2=5-3$$

$$d=2$$

$$S_n=\frac{n}{2}(2a+(n-1)d)$$

where d is the common difference and a is the first term.

$$69=\frac{3}{2}(2a+(3-1)2)$$

$$a=21$$

By

$$S_n=\frac{n}{2}(a+l)$$

$$69=\frac{3}{2}(21+l)$$

$$l=25$$

$\endgroup$
1
  • 2
    $\begingroup$ This seems unnecessarily convoluted. Why not just observe that if the first odd number is $N$, then the other two are $N+2$ and $N+4$, and so the statement is that their sum $3N+6$ equals $69$, i.e., $3N+6=69$? This leads immediately to $N=21$ and so to $N+4=25$. $\endgroup$ – MPW Aug 10 '17 at 3:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.